2014
DOI: 10.5812/iranjradiol.13547
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Findings in Patients With Acute Respiratory Symptoms That Suggest the Necessity of a Chest X-ray for Community-Acquired Pneumonia

Abstract: Background:Pneumonia is a common illness in all parts of the world and is considered as a major cause of death among all age groups. Nevertheless, only about 5% of patients referring to their primary care physicians with acute respiratory symptoms will develop pneumonia.Objectives:This study was performed to derive practical criteria for performing chest radiographs for the evaluation of community-acquired pneumonia (CAP).Patients and Methods:A total of 420 patients with acute respiratory symptoms and positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Table 2 shows a low diagnostic accuracy of auscultation for pneumonia in these patients. Supplementary Figure 5 demonstrates a higher sensitivity for the combination of different breath sounds, found by Ebrahimazedeh et al (decreased breath sounds, crackles, rhonchi), followed by crackles as a single breath sound (see Table 3) 36 .…”
Section: Pc Feb-jun 2001mentioning
confidence: 56%
See 1 more Smart Citation
“…Table 2 shows a low diagnostic accuracy of auscultation for pneumonia in these patients. Supplementary Figure 5 demonstrates a higher sensitivity for the combination of different breath sounds, found by Ebrahimazedeh et al (decreased breath sounds, crackles, rhonchi), followed by crackles as a single breath sound (see Table 3) 36 .…”
Section: Pc Feb-jun 2001mentioning
confidence: 56%
“…pneumonia. Nine prospective observational studies and two case-control studies included patients with acute respiratory symptoms or with an expected pneumonia and compared auscultation with CXR for the detection of pneumonia [35][36][37][38][39][40][41][42][43][44][45] . Table 2 shows a low diagnostic accuracy of auscultation for pneumonia in these patients.…”
Section: Pc Feb-jun 2001mentioning
confidence: 99%
“…Those that were moderate risk were only included after consideration of their limitations. 6,14,16,17,20,21 Two were case control studies 16,21 but enrolled patients prospectively in a consecutive series, and a CXR was performed on each patient. In 1 study, 17 not all patients received the reference standard CXR; those with a low probability of CAP were randomized to receive one or not.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The remaining 9 studies reported the accuracy of 18 simple heuristics that predict a dichotomous outcome of CAP versus no CAP (Appendix B4). A CDR using the presence of normal vital signs to exclude CAP was the most common, appearing in 4 studies, 15,16,20,21 while a CDR using normal vital signs plus a normal pulmonary examination to exclude CAP appeared in 3 studies. 15,16,21 Fourteen CDRs have good sensitivities (above 75%) while 12 lacked specificity (below 60%).…”
Section: Clinical Decision Rules Identifiedmentioning
confidence: 99%
See 1 more Smart Citation